Activated Microglia Disrupt the Blood-Brain Barrier and Induce Chemokines and Cytokines in a Rat in vitro Model - Shigemoto-Mogami, Yukari; Hoshikawa, Kazue; Sato, Kaoru (Frontiers in Cellular Neuroscience, 2018)
Severe neuroinflammation is associated with blood brain barrier (BBB) disruption in CNS diseases. Although microglial activation and subsequent concentration changes in cytokines/chemokines (C/Cs) are suggested to be key steps that worsen neuroinflammation, few data are available concerning the significance of the interaction of microglia with BBB cells in this process. In this study, we mimicked neuroinflammation by adding LPS-activated microglia (LPS-MG) to the abluminal side of an in vitro BBB model composed of endothelial cells (EC), pericytes (Peri) and astrocytes (Ast). We then examined the abluminal concentration changes of 27 C/Cs and the interactions between LPS-MG and BBB cells. LPS-MG caused BBB collapse, as revealed by decreases in the trans-endothelial electrical resistance (TEER) and in the expression levels of tight junction (TJ) proteins. Under these conditions, 19 C/Cs were markedly increased on the abluminal side. Unexpectedly, although LPS-MG alone released 10/19 C/Cs, their concentrations were much lower than those detected on the abluminal side of the BBB model supplemented with LPS-MG. Co-culture of LPS-MG with Ast caused marked increases in 12/19 C/Cs, while co-culture of LPS-MG with EC and Peri resulted in a significant increase in 1/19 C/Cs (fractalkine). These results suggest that C/C dynamics in neuroinflammation associated with BBB breakdown are not caused only by activated microglia but are mainly due to the interaction of activated microglia with Ast.